Compact Optical 90° Hybrid on a Thin-Film Lithium Niobate Platform Used for Integrated Coherent Transceivers - Haolei Feng; Yuqiong Chen; Zheyuan Shen; Man Chen; Hanyu Wang; Jianguo Liu; Suo Wang; Zeping Zhao (Photonics)
A 90° optical hybrid employing an MMI coupler was fabricated on a thin-film lithium niobate (TFLN) platform that can be used for integrated coherent transceivers. The fabricated 90° optical hybrid exhibited a CMRR greater than 20 dB, a phase error below ±7.5°, and an excess loss less than 1.8 dB (including contributions from the 90° hybrid, a 1 × 2 MMI coupler, and an optical delay line, after subtracting the losses from the coupler and delay line, the 90° optical hybrid introduced less than 0.9 dB of loss) over the C-band with a compact footprint of 13.8 × 250 μm2, facilitating the future development of high-bandwidth optical coherent transceivers heterogeneously integrated on TFLN.